Development and Disease-Dependent Dynamics of Spermatogonial Subpopulations in Human Testicular Tissues - Portela, Joana M. D. (J Clin Med, 2020)
Cancer therapy and conditioning treatments of non-malignant diseases affect spermatogonial function and may lead to male infertility. Data on the molecular properties of spermatogonia and the influence of disease and/or treatment on spermatogonial subpopulations remain limited. Here, we assessed if the density and percentage of spermatogonial subpopulation changes during development (n = 13) and due to disease and/or treatment (n = 18) in tissues stored in fertility preservation programs, using markers for spermatogonia (MAGEA4), undifferentiated spermatogonia (UTF1), proliferation (PCNA), and global DNA methylation (5mC). Throughout normal prepubertal testicular development, only the density of 5mC-positive spermatogonia significantly increased with age. In comparison, patients affected by disease and/or treatment showed a reduced density of UTF1-, PCNA- and 5mC-positive spermatogonia, whereas the percentage of spermatogonial subpopulations remained unchanged. As an exception, sickle cell disease patients treated with hydroxyurea displayed a reduction in both density and percentage of 5mC- positive spermatogonia. Our results demonstrate that, in general, a reduction in spermatogonial density does not alter the percentages of undifferentiated and proliferating spermatogonia, nor the establishment of global methylation. However, in sickle cell disease patients’, establishment of spermatogonial DNA methylation is impaired, which may be of importance for the potential use of this tissues in fertility preservation programs.